International Cooperation of Authoritarian Regimes: Toward a Conceptual Framework - Gero Erdmann; André Bank; Bert Hoffmann; Thomas Richter (German Institute of Global and Area Studies (GIGA), 2013)
Authoritarian regimes use multiple forms of international cooperation to sustain their rule. In scholarly research, however, the study of these phenomena has been marginal and still lacks conceptual clarity. This paper takes stock of these shortcomings and embarks on a review of the existing literature from democratization, diffusion, policy transfer and Europeanization studies. In doing so, it identifies a number of conceptual approaches whose integration can provide a useful framework for the study of the international cooperation of authoritarian regimes. For this, the specific characteristics of nondemocratic rule need to be taken into account - from their preference of some forms of cooperation over others to practical difficulties for empirical fieldwork. Against this backdrop, we provide examples of different types of authoritarian cooperation and conclude by sketching a research agenda that is as politically necessary as it is academically promising.
Keywords: 300; authoritarian regimes; international dimension; cooperation; diffusion; learning; policy transfer